PENGARUH MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE PADA MATA PELAJARAN PAI TERHADAP HASIL BELAJAR SISWA KELAS X SEMESTER GENAP SMA NEGERI 1 GENTENG - Mashuri, Imam; Fauzi, Anis; Alfiyana, Nikhla (INCARE, International Journal of Educational Resources, 2022)
This research is motivated by the tendency of most students who are less active in learning PAI in class. Students are less enthusiastic in participating in learning activities in class, pay less attention to the teacher. This study aims to determine the influence of the application of the inside outside circle learning model in PAI subjects on the learning outcomes of class X students in the even semester of SMA Negeri 1 Genteng. This type of experimental quantitative research, namely quasi experimental design with the type of control group design that uses a quantitative approach. The population includes all students of class X SMA Negeri 1 Genteng, totaling 371 students. The sampling technique applied a probability sampling technique with cluster random sampling (area sampling). The research samples were class X MIPA 1 as the experimental class, and class X MIPA 4 as the control class. Class X MIPA 3 as a research instrument trial class. Research data obtained from tests, interviews, and documentation. Based on the results of the validity and reliability tests of the student learning outcomes test instrument, which totaled 25 item questions, were declared valid and reliable. The results of the normality test using the Kolmogrov Smirnov test show that the data is normally distributed, and the homogeneity test with the one way ANOVA formula shows that the research data is a homogeneous population. The results of the analysis of simple linear regression tests in this study indicate that there is an influence of the application of the inside outside circle learning model in PAI subjects on the learning outcomes of class X students in the even semester of SMA Negeri 1 Genteng.